GENETIC VARIABILITY, CHARACTER ASSOCIATION AND PATH ANALYSIS STUDIES IN SORGHUM (SORGHUM BICOLOR L. MOENCH) - B. ARUNKUMAR, (The Bioscan, 2013)
Experiment was conducted to study the genetic variability, association among the yield component traits, their direct and indirect effects on the yield of sorghum. All the genotypes showed considerable amount of variation in their mean performances with respect to the characters studied, indicates presence of sufficient variability and scope for further selection and breeding superior and desirable genotypes.GCV played a major role for the expression of the traits. Fodder yield/plant (34.08) had high GCV, followed by Grain yield/Ha (29.88), Grain yield/plant (28.48), Ear head length (12.89), Test weight (11.04), Seed set % (10.25), Plant Height (9.05), Days 50% flowering (8.35) and Ear head breadth (8.27). Heritability in narrow sense ranged from 50.30 (ear head breadth) to 92.20 (grain yield). High GA observed for grain yield (1376.74) coupled with high heritability (92.20), indicating the preponderance of the non-additive gene action; suggesting that hybridization breeding will be effective. Ear head length (0.443) and seed set % (0.705) were positively associated with grain yield per hectare indicating any increase in these traits will increase the yield. Ear head length, test weight and seed set percent had positive direct effect on yield indicating importance of these characters, which can be strategically used to improve the yield of sorghum.